Motor Neuropathy in Hypothyroidism: Clinical and Electrophysiological Findings - Sabina Yeasmin (Bangabandhu Sheikh Mujib Medical University Journal, 2009)
Background: Hypothyroidism is a clinical condition associated with low levels of thyroid hormones with raised TSH. Peripheral neuropathy may be associated with hypothyroidism which usually develops insidiously over a long period of time due to irregular taking of drugs or lack of thyroid hormone replacement.